1885 Wis. Sess. Laws 1109, ch. 227, § 3, pt. 50 - (:unkn) unknown (My University, 1885)
Authorized the city to regulate and prohibit the carrying concealed of any pistol, revolver, sling shot, cross knuckles, knuckles of lead, brass, or other metal, Bowie knife, dirk knife, dirk, dagger, or any other dangerous or deadly weapon.
Keywords: CARRY - CONCEALED